PENGEMBANGAN MEDIA PEMBELAJARAN E-PUBLICATION MODUL TEKNIK SEPEDA MOTOR MAHASISWA PENDIDIKAN TEKNIK MESIN FKIP UNIVERSITAS SEBELAS MARET - Wisnu Dimas Sasongko; Indah Widiastuti; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
Mobile learning has become a great tool for delivering educational resources in which learners can not only access the module anytime and anywhere, but also can actively interact with the learning material. This research aims to design and develop learning material of an automotive engineering course based on mobile device for mechanical engineering education students. The development e-publication module of motorcycle mechanic course employed the ADDIE instructional design model encompassing five steps: analysis, design, development, implementation, and evaluation. The student’s learning style was identified to characterize mobile module target. It was found that majority of the students as user have auditory and kinesthetic, then the module will be designed with the design in accordance with auditory and kinesthetic learning style, therefore the module will be mainly designed on audio-based format. The learning module developed using e-publication software consisting of structured documents combined with audio and video files. Some experts were asked to evaluate the implementation feasibility of the module. The average evaluation score was 85.4%, indicating high acceptance of implementing the learning module. It implies that e-publication module delivery has the potential to gain wider acceptance in engineering education complementing the in-class and practical learning.